Continuous electrocoagulation of cheese whey wastewater: An application of Response Surface Methodology. - Tezcan Un, Umran; Kandemir, Ayse; Erginel, Nihal; Ocal, S. Eren (Journal of Environmental Management, 2014)
In this study, treatment of cheese whey wastewater was performed using a uniquely-designed continuous electrocoagulation reactor, not previously encountered in the literature. An iron horizontal rotating screw type anode was used in the continuous mode. An empirical model, in terms of effective operational factors, such as current density (40, 50, 60 mA/cm 2 ), pH (3, 5, 7) and retention time (20, 40, 60 min), was developed through Response Surface Methodology. An optimal region characterized by low values of Chemical Oxygen Demand (COD) was determined. As a result of experiments, a linear effect in the removal efficiency of COD was obtained for current density and retention time, while the initial pH of the wastewater was found to have a quadratic effect in the removal efficiency of COD. The best fit nonlinear mathematical model, with a coefficient of determination value ( R 2 ) of 85%, was defined. An initial COD concentration of 15.500 mg/L was reduced to 2112 mg/L with a removal efficiency of 86.4%. In conclusion, it can be said that electrocoagulation was successfully applied for the treatment of cheese whey wastewater.